Riboflavin induces Metarhizium spp. to produce conidia with elevated tolerance to UV-B, and upregulates photolyases, laccases and polyketide synthases genes - Pereira-Junior, R.A. (2018)
Aims: The effect of nutritional supplementation of two Metarhizium species with riboflavin (Rb) during production of conidia was evaluated on (i) conidial tolerance (based on germination) to UV-B radiation and on (ii) conidial expression following UV-B irradiation, of enzymes known to be active in photoreactivation, viz., photolyase (Phr), laccase (Lac) and polyketide synthase (Pks). Methods and Results: Metarhizium acridum (ARSEF 324) and Metarhizium robertsii (ARSEF 2575) were grown either on (i) potato dextrose agar medium (PDA), (ii) PDA supplemented with 1% yeast extract (PDAY), (iii) PDA supplemented with Rb (PDA+Rb), or (iv) PDAY supplemented with Rb (PDAY+Rb). Resulting conidia were exposed to 866·7 mW m−2 of UV-B Quaite-weighted irradiance to total doses of 3·9 or 6·24 kJ m−2. Some conidia also were exposed to 16 klux of white light (WL) after being irradiated, or not, with UV-B to investigate the role of possible photoreactivation. Relative germination of conidia produced on PDA+Rb (regardless Rb concentration) or on PDAY and exposed to UV-B was higher compared to conidia cultivated on PDA without Rb supplement, or to conidia suspended in Rb solution immediately prior to UV-B exposure. The expression of MaLac3 and MaPks2 for M. acridum, as well as MrPhr2, MrLac1, MrLac2 and MrLac3 for M. robertsii was higher when the isolates were cultivated on PDA+Rb and exposed to UV-B followed by exposure to WL, or exposed to WL only. Conclusions: Rb in culture medium increases the UV-B tolerance of M. robertsii and M. acridum conidia, and which may be related to increased expression of Phr, Lac and Pks genes in these conidia. Significance and Impact of the Study: The enhanced UV-B tolerance of Metarhizium spp. conidia produced on Rb-enriched media may improve the effectiveness of these fungi in biological control programs.